2013
DOI: 10.1111/gbb.12022
|View full text |Cite
|
Sign up to set email alerts
|

COMTrs4680 Met is not always the ‘smart allele’: Val allele is associated with better working memory and larger hippocampal volume in healthy Chinese

Abstract: Catechol-O-methyltransferase(COMT) Val158Met (rs4680) polymorphism plays a crucial role in regulating brain dopamine level. Converging evidence from Caucasian samples showed that, compared with rs4680 Val allele, the Met allele was linked to lower COMT activity, which in turn was linked to better cognitive performance such as working memory (WM) and to a larger hippocampus (a brain region important for WM). However, some behavioral studies have shown that the function of rs4680 appears to vary across different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
42
2
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(51 citation statements)
references
References 62 publications
(97 reference statements)
4
42
2
3
Order By: Relevance
“…Possible explanations for this inconsistency may include the different racial backgrounds of the samples and the different cognitive tasks used due to that many other studies have found racial differences in genetic effects (Wang et al, 2013) and that different working memory tasks have shown low inter-correlations (Conway et al, 2005). Future studies should include samples of different racial groups and use a broader range of measures to investigate whether the effect of NOS1 genetic variants is specific to some measures and samples.…”
Section: Discussionmentioning
confidence: 99%
“…Possible explanations for this inconsistency may include the different racial backgrounds of the samples and the different cognitive tasks used due to that many other studies have found racial differences in genetic effects (Wang et al, 2013) and that different working memory tasks have shown low inter-correlations (Conway et al, 2005). Future studies should include samples of different racial groups and use a broader range of measures to investigate whether the effect of NOS1 genetic variants is specific to some measures and samples.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, genetic association studies between COMT Met/Val and prefrontal cognitive functions were performed. Inconsistent results were reported for the association of the Met allele with either better ( Caldu et al, 2007;Egan et al, 2001) or worse (Buckert et al, 2012;Wang et al, 2013) cognitive performance. Considering enormous genetic heterogeneity of human population, it is not surprising to obtain contradictory results in the association studies.…”
Section: Introductionmentioning
confidence: 96%
“…Much more research is needed to examine both culture-general and culture-specific processes in genetic stratification. Closely related to this point, it should also be noted that there is growing evidence that genetic effects on behaviors may vary by ethnic/ racial groups Kimura 2011;Wang et al 2013). Much more research is needed to ascertain cultural generality or specificity of conclusions on human behaviors and their genetic and neural bases (Chiao and Cheon 2010;Henrich et al 2010).…”
Section: Discussionmentioning
confidence: 94%